ต้นทุนฐานกิจกรรมของการเยี่ยมบ้านในผู้ป่วยระยะสุดท้าย โรงพยาบาลส่งเสริมสุขภาพตาบลมะเขือแจ้ จังหวัดลาพูน - นฤศสธร ขันแก้วผาบ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Home visits are important and necessary health care service for providing continuous care to patients after hospital discharge. This descriptive study aims to analyze the activity-based cost of home visits among terminally ill patients, Tambon Makhueajae Health Promoting Hospital, Lamphun Province, and compare the activity-based cost of home visits with the reimbursement for service units from the National Health Security Fund. The conceptual framework used for Activity-Based Costing, introduced by Kaplan and Cooper (1998), is composed of four steps: 1) develop the activity dictionary, 2) determine how much the organization spending on each of its activities 3) identifying the organization’s products, services, and customers, and 4) select activity cost drivers that link activity costs to the organization’s product, services, and customers. The subjects of the study were 5 of the multidisciplinary team that provide the home visits and home visit activities for terminal ill patients from August 1, 2019 to October 31, 2019. The instruments used in this study, developed by the investigator, consisted of the activity dictionary, time spent record forms for activities, and the data record forms for labor costs, material costs and capital costs. All instruments were confirmed for objectivity by three experts and the inter-rater reliability of the two data collectors was 1.0. Data were analyzed using descriptive statistics. Results revealed that: 1. The activity-based cost of home visits among terminally ill patients by the interdisciplinary team was 1,296.38 THB, of which the ratio of labor cost: materials cost: capital cost was 62.26:37.56:00.17. The activity-based cost of home visits among terminally ill patients by the registered nurses was 876.09 THB, of which the ratio of labor cost:materials cost:capital costs was 44.15:55.57:0.26. 2. The activity-based cost of home visits among terminally ill patients and dead within 1 month, visited by the multidisciplinary team once and visited by registered nurses for 3 times, was 57.25 THB lower than the reimbursement for service units from the National Health Security Fund. The activity-based cost of home visits among terminally ill patients and dead within 2 months, visited by the multidisciplinary team twice and visited by registered nurses for 6 times, was 2,849.30 THB higher than the reimbursement for service units from the National Health Security Fund. The hospitals and nursing administrators can use the cost data from this study to calculate the break-even analysis and consider the efficacy of resource utilization of home visits among terminally ill patients.